The Drosophila nuclear receptor e75 contains heme and is gas responsive. - Reinking, J.; Lam, M.M.; Pardee, K.; Sampson, H.M.; Liu, S.; Yang, P.; Williams, S.; White, W.; Lajoie, G.; Edwards, A.; Krause, H.M. (Cell, 2005)
Nuclear receptors are a family of transcription factors with structurally conserved ligand binding domains that regulate their activity. Despite intensive efforts to identify ligands, most nuclear receptors are still "orphans." Here, we demonstrate that the ligand binding pocket of the Drosophila nuclear receptor E75 contains a heme prosthetic group. E75 absorption spectra, resistance to denaturants, and effects of site-directed mutagenesis indicate a single, coordinately bound heme molecule. A correlation between the levels of E75 expression and the levels of available heme suggest a possible role as a heme sensor. The oxidation state of the heme iron also determines whether E75 can interact with its heterodimer partner DHR3, suggesting an additional role as a redox sensor. Further, the E75-DHR3 interaction is also regulated by the binding of NO or CO to the heme center, suggesting that E75 may also function as a diatomic gas sensor. Possible mechanisms and roles for these interactions are discussed.